2010
DOI: 10.1111/j.1461-9563.2009.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change scenarios and models yield conflicting predictions about the future risk of an invasive species in North America

Abstract: 1 The pea leafminer Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae) is an invasive species in North America and a serious economic pest on a wide variety of crops. We developed a bioclimatic envelope model (BEM) for this species and examined the envelope's potential location in North America under various future climates. 2 We compared the future bioclimatic envelopes for L. huidobrensis using either simple scenarios comprising uniform changes in temperature/precipitation or climate projections from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…Mika et al . () found that GCM choice could result in prediction of areas at risk for Contarinia nasturtii that diverged not just in magnitude but also in direction of change; see also Mika & Newman (). Results such as these have worrying implications for impact research and emphasize the need for studies that investigate model dependency of projected biological impacts.…”
Section: Introductionmentioning
confidence: 97%
“…Mika et al . () found that GCM choice could result in prediction of areas at risk for Contarinia nasturtii that diverged not just in magnitude but also in direction of change; see also Mika & Newman (). Results such as these have worrying implications for impact research and emphasize the need for studies that investigate model dependency of projected biological impacts.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, CLIMEX is well suited for investigating the interactions between biological invasions and potential responses to climatic change (e.g. Mika and Newman 2010;Lozier and Mills 2011;Hill et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, two studies on the Australian Bronze bug ( Thaumastocoris peregrinus , Thaumastocoridae) using different climate modelling schemes (CLIMEX: Saavedra et al 2015 ; WorldClim 1.3: Montemajor et al 2015 ) both forecast considerable future spread of the bug, largely in association with Eucalyptus plantations, but with some differences in detail of likely intensity of invasion across the largely overlapping predicted ranges. Many such models involve predictions of a suitable 'bioclimatic envelope', but many are based on uniform increases of temperature or precipitation levels, which may render them oversimplistic (Mika and Newman 2010 ).…”
Section: Climate Changementioning
confidence: 99%